Myonuclear permanence in skeletal muscle memory: a systematic review and meta‐analysis of human and animal studies. Issue 5 (12th August 2022) - Rahmati, Masoud; McCarthy, John J.; Malakoutinia, Fatemeh
Abstract: One aspect of skeletal muscle memory is the ability of a previously trained muscle to hypertrophy more rapidly following a period of detraining. Although the molecular basis of muscle memory remains to be fully elucidated, one potential mechanism thought to mediate muscle memory is the permanent retention of myonuclei acquired during the initial phase of hypertrophic growth. However, myonuclear permanence is debated and would benefit from a meta‐analysis to clarify the current state of the field for this important aspect of skeletal muscle plasticity. The objective of this study was to perform a meta‐analysis to assess the permanence of myonuclei associated with changes in physical activity and ageing. When available, the abundance of satellite cells (SCs) was also considered given their potential influence on changes in myonuclear abundance. One hundred forty‐seven peer‐reviewed articles were identified for inclusion across five separate meta‐analyses; (1–2) human and rodent studies assessed muscle response to hypertrophy; (3–4) human and rodent studies assessed muscle response to atrophy; and (5) human studies assessed muscle response with ageing. Skeletal muscle hypertrophy was associated with higher myonuclear content that was retained in rodents, but not humans, with atrophy (SMD = −0.60, 95% CI −1.71 to 0.51, P = 0.29, and MD = 83.46, 95% CI −649.41 to 816.32, P = 0.82; respectively). Myonuclear and SC content were both lower following atrophy in humans (MD = −11, 95% CI −0.19 to −0.03, P = 0.005, and SMD = −0.49, 95% CI −0.77 to −0.22, P = 0.0005; respectively), although the response in rodents was affected by the type of muscle under consideration and the mode of atrophy. Whereas rodent myonuclei were found to be more permanent regardless of the mode of atrophy, atrophy of ≥30% was associated with a reduction in myonuclear content (SMD = −1.02, 95% CI −1.53 to −0.51, P = 0.0001). In humans, sarcopenia was accompanied by a lower myonuclear and SC content (MD = 0.47, 95% CI 0.09 to 0.85, P = 0.02, and SMD = 0.78, 95% CI 0.37–1.19, P = 0.0002; respectively). The major finding from the present meta‐analysis is that myonuclei are not permanent but are lost during periods of atrophy and with ageing. These findings do not support the concept of skeletal muscle memory based on the permanence of myonuclei and suggest other mechanisms, such as epigenetics, may have a more important role in mediating this aspect of skeletal muscle plasticity.